Undocumented migrant women in Denmark have inadequate access to pregnancy screening and have a higher prevalence Hepatitis B virus infection compared to documented migrants in Denmark: a prevalence study - Annika Wendland; Boje K. Ehmsen; Vibeke Lenskjold; Birgitte S. Astrup; Marlene Mohr; Christopher J. Williams; Susan A. Cowan (BMC, 2016)
Abstract Background Pregnant residents of Denmark are tested by their GP for current infections with Hepatitis B virus (HBV), HIV and syphilis through the Danish pregnancy screening programme to identify infections and initiate interventions to prevent mother-to-child transmission. Documented migrants (DM) have access to this screening but undocumented migrants (UM) do not, instead relying on ad-hoc care from clinics run by non-governmental organisations. We aimed to assess screening frequency in UM and to compare prevalence of infection in UM with DM. Methods We obtained individual-level information on HBV, HIV and syphilis testing frequency and results for pregnant women attending three clinics specialising in care for UM between August 2011 and August 2014. We obtained aggregate data on the prevalence of the three infections for documented migrants from the Danish pregnancy screening programme and birth register between January 2011 and January 2014. Planned abortions were excluded from the study. We described demographic features of pregnant UM and estimated the screening frequency for HIV, HBV and syphilis. We compared prevalence of current infections in UM and DM by calculating standardised prevalence ratios (SPR). Results The three UM clinics registered 219 pregnancies qualifying for screening. Overall 43, 58 and 60 % of pregnant UM had a test result recorded for HBV, Syphilis and HIV respectively, compared to >99 % in the general Danish population including DM. The prevalence of HBV was higher in UM than in DM (SPR: 2.4; 95 % CI: 1.1-5.3). The SPR of 2 (95 % CI: 0.5-8.0) for HIV was not statistically significant, potentially due to small sample size of UM. None of the pregnant UM tested positive for Syphilis. Conclusions Pregnant UM have a poorer chance of being tested for HIV, HBV and syphilis, despite having a higher prevalence of HBV than DM. We recommend giving systematic access to routine pregnancy screening to all UM to prevent mother-to-child transmission and to address the observed health care inequity.